Innovation of HOTS Assessment Instruments in Science Learning: A Game-Based Approach in Islamic Primary Schools - Ridho, Ali; Andry Budianto, Ahmad (Journal of Islamic Elementary Education, 2024)
This study aims to develop a game-based assessment instrument in science learning in Islamic Elementary Schools, which can measure students' high-level thinking skills (HOTS). The instrument is designed to create an interactive and engaging learning experience for students, as well as integrate science concepts with Islamic values. The development model used is ADDIE (Analysis, Design, Development, Implementation, Evaluation), with trials carried out in grades 4-6 in several Islamic Elementary Schools. The results show that game-based assessment instruments successfully increase student engagement in learning, as well as be effective in measuring critical, creative, and analytical thinking skills. In addition, this instrument has also been proven to enrich students' understanding of the science studied, as well as strengthen relevant Islamic values. The application of this assessment instrument is expected to improve student learning outcomes in the field of science and help develop higher-order thinking skills.